Efficacy of Autologous Platelet-Rich Plasma (PRP) on Perineal Wound Healing: A Controlled Non-Randomized Clinical Trial. - Muhammad Fadli; Bobby Indra Utama; Hirowati Ali (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Perineal wounds are a very common complication of vaginal birth. Perineal trauma associated with childbirth is defined as damage to the skin, perineal muscles, as well as the sphincter and anal epithelium complex. This study aims to determine the effect of PRP use on perineal wounds. Method: A single-center, controlled, non-randomized, non-blinded clinical trial was designed in patients with perineal wounds after vaginal delivery. PRP was taken from each patient's serum (autologous). Perineal wound healing after intervention was assessed using the Redness, Oedema, Ecchymosis, Discharge, Approximation (REEDA) scale. Perineal wound pain was assessed using the Visual Analog Scale (VAS). Result: The current study involved 56 samples, 28 people per group. The average age of the patients was 28.38 ± 6.280 years. The highest education was high school, 42.9%, while the lowest was elementary school (21.4%). The highest VAS scale was 3 (42.9%) and the lowest was 1 (5.4%). The prevalence of the highest degree of perineal wounds in general was degree 2 (98.2%). The highest score was in the moderately healed group on PRP administration (92.9%). In contrast to the control group, the mildly healed category was 21.4% and not healed 14.4%. Conclusion: There is a significant relationship between the PRP to healing perineal wounds in vaginal delivery patients at the Seberang Padang Health